On the Annyversary Discourse and its Genres - Soboleva, M.Y. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
This article attempts to make a primary definition of the jubilee concept. We introduce the "Jubilee discourse" concept which is limited by "Time" and "Situation" parameters. This type of discourse is illustrated by an example of the discourse related to the twentieth anniversary of the Fall of the Berlin Wall. Genres of the jubilee celebration are highlighted.
Keywords: jubilee; jubilee discourse; discourse; event; genre of discourse